Religious Moderation in the Islamic Religious Education Curriculum: A Sharia Study in the Global Context: Penelitian - Muhammadong; Khaerunnisa; Nurhilaliyah; Farhah Utami; Sitti Muthmainnah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to examine the incorporation of religious moderation within the Islamic Religious Education (PAI) curriculum, emphasizing Sharia values in the framework of globalization. In a time when people are becoming more diverse and connected, it is important to know how to use religious moderation in schools to promote tolerance and fight extremism. The study utilizes a qualitative methodology, specifically a literature review, to examine pertinent sources, including the perspectives of Islamic scholars, educational practices, and the notion of religious moderation as defined in Sharia. The findings demonstrate that religious moderation in the PAI curriculum functions as a crucial instrument for reconciling religious teachings, fostering tolerance, and advancing inclusion amid global difficulties. It shows how important it is to have a curriculum that supports universal Sharia principles and helps create a generation that is moderate, accepting, and open-minded. The study also shows that while there are problems with putting religious moderation into practice, it is important to include it in the PAI curriculum to stop people from becoming radicalized and to promote peaceful coexistence. The results show how important it is to include religious moderation in education to create a peaceful world.